Perancangan Aset Animasi 2D Pixel “Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain” dalam Mobile Game - Farraz Nabila; Nusrito Zalins Adekory (YASIN, 2026)
Although advances in digital media offer new opportunities for cultural preservation through educational games, the design of visual assets that specifically represent Tingkuluak in a pixel art style remains limited. This study aimed to design 2D pixel art animation assets for the mobile game “Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain” as a medium for introducing Minangkabau culture to younger generations. The study employed a qualitative descriptive approach with a design process based on the Game Development Life Cycle (GDLC). Data were collected through a semi-structured interview with one customary informant, a questionnaire administered to 101 respondents, a literature review, visual documentation, alpha testing by one expert, and beta testing involving five users. The data were analyzed using qualitative descriptive analysis and descriptive statistics encompassing frequencies, percentages, and mean scores. The results of the study produced character, environment, property, interface, mini-game, and five types of Tingkuluak assets with a consistent visual style. The beta-testing results showed mean scores of 5.00 for suitability as an educational medium, 4.80 for game attractiveness, and 4.20 for the comfort of character animation. These findings reinforce the potential use of pixel art and GDLC in the development of culture-based digital media. This study confirms that cultural representation accuracy, visual readability, and interactivity are important aspects of educational game asset design and provides practical implications for developing cultural preservation media that appeal to younger generations. Further refinement of the animations and testing with broader user groups are required to improve the quality and acceptability of the product.